A review of psyllium plant - H Naghdi Badi; A Dastpak; SA Ziai (Institue of Medicinal Plants, ACECR, 2004)
Genus Plantago belongs to Plantaginaceae family. It has two important medicinal species, P. ovata Forsk. and P. psyllium L., named in common psyllium. In traditional medicine, the husk of this plant used as laxative. Recent studies have shown that the hydrocholoidal fiber of the husk has antidiabetic and antihypercholestrolemia effects. Also it has been shown that it could reduce the prevalence of colon cancer. This plant is safe and has not any serious side effects. In this article we review the uses and benefits of this plant, which grows in many parts of Iran.